2017
DOI: 10.1021/acs.inorgchem.6b02758
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Methane–Framework Interaction by Controlling Pore Size and Functionality of Pillared MOFs

Abstract: The rational design of functionalized porous metal-organic frameworks (MOFs) for gas adsorption applications has been applied using three spacer ligands HDPT (3,6-di(pyridin-4-yl)-1,4-dihydro-1,2,4,5-tetrazine), DPT (3,6-di(pyridin-4-yl)-1,2,4,5-tetrazine), and BPDH (2,5-bis(4-pyridyl)-3,4-diaza-2,4-hexadiene) to synthesize TMU-34, [Zn(OBA)(HDPT)]·DMF, TMU-34(-2H), [Zn(OBA)(DPT)]·DMF, and TMU-5, [Zn(OBA)(BPDH)]·1.5DMF, respectively. By controlling the pore size and chemical functionality of these three MOFs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 49 publications
(69 reference statements)
1
52
0
Order By: Relevance
“…The MOF, [Zn(OBA)(H 2 DPT) 0.5 ] ⋅ DMF (TMU‐34), was easily synthesized on a large scale at low cost by a sonochemical reaction, as described in detail in the Experimental Section, starting from zinc acetate, H 2 OBA, and H 2 DPT (Scheme ). A powder XRD pattern of the obtained TMU‐34 showed that the sonochemical synthesis gave a material that was structurally identical to that prepared by a solvothermal method (Figure S1) …”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The MOF, [Zn(OBA)(H 2 DPT) 0.5 ] ⋅ DMF (TMU‐34), was easily synthesized on a large scale at low cost by a sonochemical reaction, as described in detail in the Experimental Section, starting from zinc acetate, H 2 OBA, and H 2 DPT (Scheme ). A powder XRD pattern of the obtained TMU‐34 showed that the sonochemical synthesis gave a material that was structurally identical to that prepared by a solvothermal method (Figure S1) …”
Section: Resultsmentioning
confidence: 79%
“…TMU‐34 is based on a binuclear Zn 2 unit, which is tetrahedrally coordinated by six carboxylate O atoms from OBA ligands to construct 2D sheets. The 2D sheets are connected through the linear H 2 DPT, extending the structure in three dimensions (Scheme ) . TMU‐34 is doubly‐interpenetrated and shows one‐dimensional 5.4×6.2 Å pores including the van der Waals radii.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of pillar spacers : 3,6‐Di(4‐pyridyl)‐1,4‐dihydro‐1,2,4,5‐tetrazine (H 2 DPT) and 1,4‐bis(4‐pyridyl)‐2,3‐diaza‐1,3‐butadiene (BPDB), used as spacers, were synthesized according to the procedures reported previously …”
Section: Methodsmentioning
confidence: 99%
“…General procedure for the Henry condensation reaction : To examine the roles of porosity and functionality of the synthesized frameworks, TMU‐4, TMU‐34, SALE‐TMU‐34, and USALE‐TMU‐34, were employed in Henry condensation reactions. All the samples were activated before the catalytic tests according to the reported procedure …”
Section: Methodsmentioning
confidence: 99%